Hannah Arendt i badanie antysemityzmu. Antysemityzm jako totemizm - Tokarska-Bakir, Joanna (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
This article is based on the available philosophical and historical Holocaust studies and offers a critical review of the reception of Hannah Arendt’s philosophical concepts of antisemitism and Jewish history, including Shoah.